An HFman probe-based reverse transcription loop-mediated isothermal amplification (RT-LAMP) assay for HIV-1 detection. (August 2022) - Zhang, Xiaoling; Li, Hanping; Liu, Ziwei; Zhao, Yongjuan; Zeng, Yi; Dong, Yajuan; Li, Lin; Zhang, Chiyu
Abstract: Loop-mediated isothermal amplification (LAMP) is suitable for the development of a rapid and cost-effective nucleic acid technique for point of care (POC) applications. However, LAMP methods often generate non-specific amplification, therefore inevitably resulting in false positive results especially when sequence-independent dyes are used to indirectly reflect the results. In this study, we established and optimized a reverse transcription LAMP (RT-LAMP) assay with a high-fidelity DNA polymerase-mediated fluorescent probe (HFman probe) for human immunodeficiency virus-1 (HIV-1) detection. The assay showed high sensitivity and specificity. Using 101 plasma samples with different HIV-1 viral load, we demonstrated that our assay can detect the major HIV-1 subtypes circulating in China, including CRF01_AE, CRF07_BC, CRF08_BC, CRF55_01B, and unique recombinant forms (URFs). We also compared our assay with an approved commercial real-time quantitative polymerase chain reaction (RT-qPCR) kit and found the sensitivity, specificity and consistency was 88.8%, 100% and 89.1%, respectively. The HFman probe-based RT-LAMP assay is a high specific detection method that is rapid, variant-tolerant and simple to operate, and thus is of great significance for timely disclosure of HIV status and rapid POC diagnosis. Graphical abstract: Image 1 Highlights: An HFman probe-based RT-LAMP assay was developed for specific detection of HIV-1. The assay is rapid, variant-tolerant, sensitive and specific. The assay can detect various HIV-1 subtypes and recombinants circulating in China. Clinical evaluation showed a well consistency between the novel RT-LAMP assay with commercial RT-qPCR kit.